Pyrolysis Characteristics of Different Humectant at High Temperature - Zhao, Yu; Ding, Lin; Liu, Jinyun; Yang, Huawu; Yin, Xinqiang; Tuo, Suxing; Zhang, Qiugen (Asian Journal of Chemistry, 2014)
Humectants is indispensable in the cigarettes. The pyrolysis characteristics of different humectant have a great significance to reduce the noxious substance which come from cigarette smoke. In this paper, experimental process is based on simulates cigarette combustion. Further research on pyrolysis of several major humectants. GC-MS analysis of products retrieved from pyrolysis reaction shows that glycol, glycerin and 27664 are prone to evaporate during pyrolysis due to its low boiling point and chemical instability, instead of vaporization, xylitol and sorbitol pyrolyzed into aldehyde, ketone and alcohol.